Solve the equation dy/dx= -(x2+y2)/xy
Let us solve the equation "\\frac{dy}{dx}= -\\frac{x^2+y^2}{xy}" using the transformation "y=ux." Then "\\frac{dy}{dx}=\\frac{du}{dx}x+u," and hence we get the equation "\\frac{du}{dx}x+u= -\\frac{1+u^2}{u}," which is equivalent to "\\frac{du}{dx}x= -\\frac{1+u^2}{u}-u," and hence to "\\frac{du}{dx}x= -\\frac{1+2u^2}{u}."
It follows that
"\\frac{udu}{1+2u^2}= -\\frac{dx}{x}"
"\\int\\frac{udu}{1+2u^2}= -\\int\\frac{dx}{x}"
"\\frac{1}{4}\\int\\frac{4udu}{1+2u^2}= -\\int\\frac{dx}{x}"
"\\int\\frac{d(1+2u^2)}{1+2u^2}= -4\\int\\frac{dx}{x}"
"\\ln(1+2u^2)= -4\\ln|x|+\\ln|C|"
"\\ln(1+2u^2)+4\\ln|x|=\\ln|C|"
"\\ln(x^4(1+2u^2))=\\ln|C|"
"x^4(1+2u^2)=C"
"x^4(1+2(\\frac{y}{x})^2)=C"
We conclude that the general solution of the equation "\\frac{dy}{dx}= -\\frac{x^2+y^2}{xy}" is
"x^4+2x^2y^2=C"
Comments
Leave a comment